Intradermal tranexamic acid microinjections: a novel treatment option for erythematotelangiectatic rosacea. (25th May 2021) - Daadaa, Najla; Litaiem, Noureddine; Karray, Manel; Bacha, Takwa; Jones, Meriem; Belajouza Noueiri, Colandane; Goucha, Samia; Zeglaoui, Faten
Abstract: Background: Treatment options for erythematotelangiectatic rosacea (ETR) are still scarce. Tranexamic acid (TXA) is an antifibrinolytic drug that was recently used for the treatment of ETR. Aims: To evaluate the efficacy and safety of intradermal microinjections of TXA for ETR. Patients/Methods: This was a retrospective study enrolling patients, treated with TXA intradermal microinjections for ETR, from January 2019 to February 2020. Response to treatment was assessed based on subjective symptoms, clinical photographs, and the Investigator Global Assessment of Rosacea Severity Score (IGA‐RSS). Results: Six patients were included. The mean number of monthly intradermal TXA microinjections was 5.1 ± 1.3. The mean decrease of IGA‐RSS was 2.4 ± 0.5. Local side effects, mainly transient erythema and swelling, were noticed in three cases. No systemic effects were noted. Clinical improvement, in respondent patients, lasted after 3 months of follow‐up. Conclusion: Intradermal TXA microinjections are a safe and effective treatment option for ETR. The optimal number of monthly sessions has yet to be determined.